Enrichment pending appeal re-examining Article 229 (223) of the Labor Code (2017)
In cases of illegal dismissal, the Labor Code mandates that judgment awards by the Labor Arbiter in favor of employees are immediately executory to "ensure the survival or even the life of the dismissed or separated employee and their family." The money judgment is supposed to provide them with economic support as the case progresses on appeal. The Supreme Court has ruled that a refund would be injurious to the employee who has relied on the money award pending appeal. However, an examination of jurisprudence shows employees with high disposable incomes benefit from the no-refund doctrine despite the lack of urgency for financial support. This paper argues that the no-refund doctrine as applied to Salaried Employees, as opposed to Wage Earners, is greatly injurious to small-to-medium enterprises. These businesses are also entitled to their own rights under Article XIII, Section 3(3) of the Constitution. Therefore, this paper argues that the constitutional mandate of promoting social justice is better fulfilled by fine-tuning the no refund doctrine in the interest of balancing the rights of labor and capital.
Keywords: Labor Code of the Philippines; Tax refunds